The Meaning of Sipakatau Sipakalebbi Sipakainge in Wajo (A Semantical Analysis) - Abdollah Abdollah; Mustakim Sulo (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
This study raises issues about what it means and how to apply sipakatau, sipakalebbi, sipakainge in Bugis culture. This study aimed to get an idea of the meaning sipakatau, sipakalebbi, sipakainge, in Bugis culture and to know how it is applied in Bugis culture. There were two benefits in this study, the benefits of theoretical and practical benefits. The model of this research was qualitative models. The stages in this study were under preparation, data collection, and data processing stages. Data were analyzed based on the words, sentences and paragraphs. Analysis of the data in this study presented informally, by formulating with ordinary words. The result of this study indicate that the meaning of sipakatau is mutually humanizing, sipakalebbi is mutual understanding or respect and sipakainge is remind each other. Based on the observations stated sipakatau, sipakalebbi, sipakainge days ago still heal tightly by Bugis community of Wajo, because they think that this culture that has a message from the ancestors. Whereas in the present, in urban culture, the bugis culture is heading to extinct due to globalization, but in rural areas there is still a applied well.